2001
DOI: 10.1074/jbc.m008283200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Preferential Assembly of Heparan Sulfate on Glypican-1

Abstract: Glypicans are major cell surface heparan sulfate proteoglycans, the structures of which are characterized by the presence of a cysteine-rich globular domain, a short glycosaminoglycan (GAG) attachment region, and a glycosylphosphatidylinositol membrane anchor. Despite strong evolutionary conservation of the globular domains of glypicans, no function has yet been attributed to them. By using a novel quantitative approach for assessing proteoglycan glycosylation, we show here that removal of the globular domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 35 publications
1
70
0
1
Order By: Relevance
“…Recent studies, however, showed that the clear-cut identification of an SG consensus sequence as a glycosylation site or the prediction of the type of glycosylation at a specific site is impossible. Some peptide domains distant to the SG sites were shown also to be important in the glycosylation (23,24). Furthermore, the fact that endogenous and recombinant chick collagen XVIII is different in its GAG glycosylation suggests that additional regulatory factors such as the cell type in which the protein is expressed and cell culture conditions are also important for glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, showed that the clear-cut identification of an SG consensus sequence as a glycosylation site or the prediction of the type of glycosylation at a specific site is impossible. Some peptide domains distant to the SG sites were shown also to be important in the glycosylation (23,24). Furthermore, the fact that endogenous and recombinant chick collagen XVIII is different in its GAG glycosylation suggests that additional regulatory factors such as the cell type in which the protein is expressed and cell culture conditions are also important for glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic residues (aromatic and aliphatic) in close proximity to the Ser-Gly attachment site have been proposed to be an enhancer element for HS assembly. In addition, the sequence distant from the GAG attachment site, for example, on the glypican core protein, has a profound influence for selectively assembling an HS chain (34). In this context, it has been hypothesized that modifications of the linkage region tetrasaccharide may be involved in the selective assembly of CS and HS chains on the linkage region (14,35,36).…”
Section: Selectivity Of the Extension Of The Linkage Region By Gag Glmentioning
confidence: 99%
“…Our observations that EXTL2 and EXTL3 transferred a GlcNAc residue to chemically synthesized disaccharides with a hydrophobic aglycon, but not to GlcA␤1-3Gal␤1-3Gal␤1-4Xyl␤1-O-Ser, are consistent with this concept. In addition, the importance of distant regions from the GAG attachment sites also has been emphasized recently in the preferential addition of HS chains (50): the cysteine-rich globular domain of glypican-1 is as much indispensable as the GAG attachment region to direct HS synthesis. If either EXTL3 or EXTL2 becomes associated with either EXT1 or EXT2, HS and͞or Hep chains possibly might be initiated and polymerized efficiently on the tetrasaccharide core.…”
Section: Figmentioning
confidence: 99%